The mid-Pliocene climate simulated by FGOALS-g2 - W. Zheng; Z. Zhang; L. Chen; Y. Yu (Geoscientific Model Development, 2013)
Within the framework of Pliocene Model Intercomparison Project (PlioMIP), the mid-Pliocene warm period (mPWP – 3.264–3.025 Ma BP) climate simulated by the Flexible Global Ocean–Atmosphere–Land System model grid-point version g2 (FGOALS-g2) are analysed in this study. Results show that the model reproduces the large-scale features of the global warming over the land and ocean. The simulated mid-Pliocene global annual mean surface air temperature (SAT) and sea surface temperature (SST) are 4.17 and 2.62 °C warmer than the preindustrial simulation, respectively. In particular, the feature of larger warming over mid–high latitudes is well captured. In the simulated warm mid-Pliocene climate, the Atlantic Meridional Overturning Circulation (AMOC) and El Niño-Southern Oscillation (ENSO) become weaker.